Analysis of Students' Errors in Solving Algebraic Story Problems Based on Newman's Procedure: A Case Study in Junior High School - Saputra, Sandy; Anggraini, Anggraini; Sugita, Gandung; Idris, Mustamin (FKIP Universitas Lampung, 2025)
This study aims to obtain a description of student errors in solving algebraic form story problems based on Newman's procedure in junior high school. This type of research is descriptive using a qualitative approach. This research uses Newman's error analysis. The subjects of this study were three students, each of whom had high mathematical ability (ST), medium mathematical ability (SS), and low mathematical ability (SR) selected from class VIII W.R Supratman based on the report card value of mathematics class VII odd semester 2023/2024. The results of this study are as follows: Students with high mathematical ability (ST) tend to make mistakes at the reading stage by not reading the problem completely, especially the symbol